2022
DOI: 10.1038/s41598-022-06847-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypsometric changes in urban areas resulting from multiple years of mining activity

Abstract: The impact of multiple years of underground mining of minerals on changes in the elevation of an urban area has been evaluated using the case study of Bytom in southern Poland. Between 1883 and 2011, that city experienced changes in absolute minimum (from 250.0 to 243.0 m a.s.l.) and maximum (from 340.0 to 348.4 m a.s.l.) elevations. During that period, the difference between minimum and maximum elevations increased from 90.0 to 105.4 m. The consequence of underground mining has been the formation of extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…In this case, the Geographic Information System (GIS) may be based on the usage or the generation of digital elevation models (DEMs), which, thanks to interpolation algorithms, allow for obtaining digital terrain models (DTMs) and their derivatives. It applies to remote sensing, geodetic data, and relief reconstruction methods based on digitising contours from archival cartographic materials 44 , 45 . DEMs of Difference (DoDs) allow the study of land surface changes in different time intervals and with different model resolutions, depending on the accuracy of the source materials.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the Geographic Information System (GIS) may be based on the usage or the generation of digital elevation models (DEMs), which, thanks to interpolation algorithms, allow for obtaining digital terrain models (DTMs) and their derivatives. It applies to remote sensing, geodetic data, and relief reconstruction methods based on digitising contours from archival cartographic materials 44 , 45 . DEMs of Difference (DoDs) allow the study of land surface changes in different time intervals and with different model resolutions, depending on the accuracy of the source materials.…”
Section: Introductionmentioning
confidence: 99%
“…The latter's tunnelling occurred from May 2012 to May 2015, resulting in a discernible settlement trough aligned east-west across central London [24,25]. In addition to the United Kingdom, InSAR has been utilised to monitor tunnelling projects in countries like India [26][27][28][29], China [30][31][32], Germany [33], Italy [34], Spain [35], the United States [36,37], Turkey [38], Vietnam [39], Poland [40][41][42], and others. Although researchers have utilised InSAR for studying surface deformation, and some of these studies have been summarised in Table 1, it is important to note that the list provided in the table is not exhaustive.…”
Section: Introductionmentioning
confidence: 99%
“…Karst is known at least locally (and sometimes quite extensively) in almost all areas underlain by evaporites, and some of these karst features involve significant subsidence [ 10 ]; Lee et al dealt with the characteristics of subsidence and the relationships between the subsidence factors over abandoned coal mines in South Korea. The subsidence factors that were investigated were the dip angle and thickness of the coal bed, mining depth, depth of subsidence and subsidence area in 548 cases of subsidence that occurred throughout the country [ 11 ]; Solarski et al used the case study of Bytom in southern Poland to evaluate the impact of multiple years of underground mining of minerals on changes in the elevation of an urban area, and concluded that the rate of anthropogenic subsidence in the city between 1883 and 2011 averaged 43 mm/year (5.5 m over the study period) [ 12 ]; Marschalko et al identified the mutual connections between mined-out panels of a deposit and the final manifestations on the ground surface related to deep black coal mining [ 13 ]; Dang et al applied the Persistent Scatterer Interferometric Synthetic Aperture Radar (PSInSAR) approach to 56 Sentinel-1A images, captured from June 2015 to June 2019 in order to map the spatial distribution of this phenomenon and monitor its evolution over the time [ 14 ]; Can et al identified the effects of mining subsidence on masonry buildings in the mining area of Kozlu, Zonguldak, Turkey, and illustrated them with selected images of damaged masonry buildings [ 15 ]; Zhang Qing et al established a model of the interaction between the building foundation and the ground, and calculated the change mechanism of the additional stress of the surrounding buildings caused by the excavation of the foundation pit and the coordination of the building with the ground by choosing a reasonable foundation subsidence equation or using the actual measured subsidence data [ 16 ]; Unlu et al used a new surface subsidence prediction method (ISP-Tech technology) to obtain geological cross-sections using geological information collected from GIS and MIS systems to build a finite element model grid, and then performed a two-dimensional finite element simulation analysis of the ground subsidence caused by mining, and compared the ground subsidence predicted by the simulation study with GPS and D-InSAR technology measurements, successfully demonstrating that the ISP-Tech technology can be applied to complex mine subsidence problems with higher prediction accuracy [ 17 ]; Ma et al, in order to investigate the effect of surface subsidence in mining areas on surface buildings, studied reinforced concrete frame structures with different differential subsidence types using SAP2000 software, ultimately showing that damage caused by uneven subsidence will inevitably reduce the seismic performance of buildings in subsidence areas [ 18 ]; Zhou Junjie established a three-dimensional finite element calculation model of “tunnel-soil-ancient building” and investigated the current status of ancient buildings such as the small building at Tianxiang, the Confucian Temple and the North Temple tower and analyzed the geological data of the site, and then evaluated the impact of surface subsidence caused by the shield construction on the above three ancient buildings [ 19 ]; Song et al used gray correlation analysis to analyze the relationship between the maximum surface subsidenc...…”
Section: Introductionmentioning
confidence: 99%